Systemic Evaluation on the Pharmacokinetics of Platinum-Based Anticancer Drugs From Animal to Cell Level: Based on Total Platinum and Intact Drugs - Qin, Zhiying; Ren, Guanghui; Yuan, Jinjie; Chen, Huili; Lu, Yang; Li, Ning; Zhang, Yongjie; Chen, Xijing; Zhao, Di (Frontiers in Pharmacology, 2020)
Cisplatin, carboplatin and oxaliplatin are the common platinum-based anticancer drugs widely used in the chemotherapeutic treatment of solid tumors in clinic. However, the comprehensive pharmacokinetics of platinum-based anticancer drugs has not been fully understood yet. This leads to many limitations for the further studies on their pharmacology and toxicology. In this study, we conduct a systemic evaluation on the pharmacokinetics of three platinum analogues at animal and cell levels, with quantification of both total platinum and intact drugs. A detailed animal study to address and compare the different pharmacokinetic behaviors of three platinum analogues has been conducted in three biological matrices: blood, plasma and ultrafiltrate plasma. Carboplatin showed an obviously different pharmacokinetic characteristic from cisplatin and oxaliplatin. On the one hand, carboplatin has the highest proportion of Pt distribution in ultrafiltrate plasma. On the other hand, carboplatin has the highest intact drug exposure and longest intact drug elimination time in blood, plasma and ultrafiltrate plasma, which may explain its high hematotoxicity. Additionally, the cellular and subcellular pharmacokinetics of oxaliplatin in two colon cancer HCT-116/LOVO cell lines has been elucidated for the first time. The biotransformation of intact oxaliplatin in cells was rapid with a fast elimination, however, the generated platinum-containing metabolites still exist within cells. The distribution of total platinum in the cytoplasm is higher than in the mitochondria, followed by the nucleus. Enrichment of platinum in mitochondria may affect the respiratory chain or energy metabolism, and further lead to cell apoptosis, which may indicate mitochondria as another potential target for efficacy and toxicity of oxaliplatin.